MODERASI DAKWAH DI ERA DISRUPSI (Studi tentang Dakwah Moderat di Youtube) - Faisal Muzzammil (Tatar Pasundan: Jurnal Diklat Keagamaan, 2021)
This study aims to reveal more about: (1) Moderate Da'wah accounts on Youtube; (2) Moderate preachers on Youtube; (3) Format of Da'wah Content on Youtube. Based on the results of data mining and analysis, several findings were obtained: (1) Three moderate da'wah accounts on Youtube are GusMus Channel with soothing content, CakNun.Com with philosophical content, and Santri Gayeng with traditional content. (2) Three moderate preachers identified on Youtube are Gus Mus with a humanist preaching approach, Cak Nun with a logical preaching approach, and Gus Baha with a millennialist approach to preaching. (3) Three formats of da'wah content on Youtube are short tausiyah format, dialogical discussion format, and lyric video format. There are two recommendations from the results of this study: (1) As a reference for preachers and Muslim content creators in conveying Islamic da'wah messages on social media, especially YouTube, to make it more universal, inclusive and moderate; (2) As a basic framework for academics, social media literacy activists, and Muslim intellectuals, including related stakeholders such as Ministry of Religion Affairs Republik Indonesia in creating and developing an ideal form of religious moderation. Keywords: Moderate Da'wah; Era of Disruption; Youtube content.